In vitro study of Phytic acid effect on p53 protein in cancer line - Rafal Hussamildeen Abdullah (College of Pharmacy / Mustansiriyah University, 2012)
Studying Phytic acid cytotoxic effect on cancer cell line showed that it is a concentration dependant effect on cancer cell line in compare with control, also have effect on the production of p53 protein using protein detection method using Eliza. The concentration of p3 protein is decreased in Vero with no significant effect (34 pg/ml ± SD 4) compare with control (64pg/ml ±SD 4) p > 0.05. Radomyosarcoma cell line (232 pg/ml± SD 32) shows a significant increase in compare with control (686 pg/ml ± SD 86) p> 0.05. The production of p53 increase in Glioblastoma- Multiforme cell (118 pg/ml ± SD 18) in compare with control (38 pg/ml ± SD 8), while the p53 quantity was not affected in the Ahmed Mohamed Nahi 3 (40 pg/ml± SD 10) compare with control (44 pg/ml ± SD 4) p>0.05.which show a different inhibition mechanisms of action on cancer cell line.